PENCIPTAAN READY TO WEAR DELUXE APLIKASI BATIK TULIS MOTIF DIPHA KIRANA - Sayidah, Deda Nur; Suharno, Suharno; Marlianti, Mira (Institut Seni Indonesia Padangpanjang, 2024)
This deluxe ready to wear is made to be a hope and prayer for the wearer, namely to be a light in the surrounding environment. Therefore, the author made the “Dipha Kirana” motif, which is a lamp motif inspired by the shape of a typical European chandelier as the main motif. The makrame technique is applied to this collection to enhance the appearance and create interesting accents that make this collection appear different and unique. The visual reference of this work is the fashion trend 2024/2025, namely Heritage sub-theme Reminiscence. The visuals represent traditional and modern forms constructed with traditional-modern techniques and materials, collaborating traditional icons, and designed for modern utility. To realize the work, the method of creation used is the method of exploration, design, and realization. The result of this work is 4 (four) ready to wear deluxe and 2 of them are displayed in the fashion show at Jakarta Muslim Fashion Week (JMFW) 2024